Eco Enzyme Sebagai Solusi Ramah Lingkungan: Model Pembelajaran Berbasis Proyek dalam Pengabdian kepada Masyarakat - Marhamah Marhamah; Muhammad Khairul Wazni; Sarwati Sarwati; Sitti Rohmi Djalilah; Hartini Haritani (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve students’ and teachers’ knowledge and skills in producing Eco Enzymes as an environmentally friendly solution through project-based learning at MA Muallimat NWDI Pancor. The program applies a Participatory Rural Appraisal (PRA) approach involving 65 students and three biology teachers. Evaluation data are collected using questionnaires and analyzed descriptively. The results show that 96% of students understand the concept of Eco Enzymes, 94% comprehend their benefits, 93% demonstrate adequate skills in the Eco Enzyme production process, and 96% exhibit positive environmental attitudes, particularly in converting organic waste into Eco Enzymes. These findings imply that teachers and students are capable of processing locally available organic waste into beneficial Eco Enzyme products, thereby supporting environmentally sustainable practices.